2015
DOI: 10.1177/0308518x15595899
|View full text |Cite
|
Sign up to set email alerts
|

When Participatory Forest Management makes money: insights from Tanzania on governance, benefit sharing, and implications for REDD+

Abstract: Participatory Forest Management (PFM) and the more recent framework for Reducing Emissions from Deforestation and Forest Degradation (REDD+) are two resource management strategies that were introduced in part for their cobenefits, including forest protection, employment opportunities, and added income for forest adjacent communities. In this paper we examine the early implementation of PFM in Tanzania's Kilwa District, led and promoted by the nongovernmental organisation Mpingo Conservation and Development Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Similarly, climate change funds in Peru led to multiple new titling programs in the Amazon (Lozano Flores, 2018). REDD+ projects supported the reinterpretation of the land law to recognize village land rights in Tanzania (see Khatun et al, 2015). However, the increase in the percentage of forests under private ownership, as reported in Table 2, risks undermining pending claims for the recognition of customary rights to forests (RRI, 2018).…”
Section: Process: Carbon Forestry's Engagement With Decentralization mentioning
confidence: 99%
“…Similarly, climate change funds in Peru led to multiple new titling programs in the Amazon (Lozano Flores, 2018). REDD+ projects supported the reinterpretation of the land law to recognize village land rights in Tanzania (see Khatun et al, 2015). However, the increase in the percentage of forests under private ownership, as reported in Table 2, risks undermining pending claims for the recognition of customary rights to forests (RRI, 2018).…”
Section: Process: Carbon Forestry's Engagement With Decentralization mentioning
confidence: 99%
“…Sikor (2013) critiques this separation of 'safeguards' from the broader 'technical' design of REDD+, arguing that MRV and other REDD+ technologies of transparency themselves play a central role in shaping the distribution of rights and benefits. Fundamentally, the implementation of REDD+ cannot be separated from the broader governance contexts in which it falls, or from the priorities of those tasked with its enactment on the ground (Khatun et al 2015, Kull et al 2015. This intersection of the global and the local has social impacts much less transparent and amenable to international monitoring than changes in forest cover.…”
Section: The Rule Of Law Accountability Transparency and Access To mentioning
confidence: 99%
“…In many settings where decentralization has taken place, women are underrepresented in forest user committees. Cases from Burkina Faso (Khatun et al 2015) illustrate that men disproportionately engage in decision-making in decentralized forest governance systems, which often has ramifications on the types of rules adopted and their enforcement, both of which typically benefit men and their forest use activities, which often center on timber harvesting However, these disparities are starting to change in some locations, and various authors have identified factors that can improve women's engagement with forest governance. In Nepal, interventions designed to make decision-making processes more inclusive have increased women's participation in local forest governance (Maskey et al 2006, McDougall et al 2013b.…”
Section: Decentralized Managementmentioning
confidence: 99%